Backlight module - LIN XINWU (2014)
A backlight module includes a light guide plate, a first light source device, and a second light source device. The first light source device is disposed adjacent to a first side surface of the light guide plate and has at least one first polarized light source for emitting a first polarized light beam. The second light source device is disposed adjacent to a second side surface of the light guide plate and has at least one second polarized light source for emitting a second polarized light beam. The light guide plate includes a first polarized light transmitting region adjacent to the second light source device and a second polarized light transmitting region adjacent to the first light source device.